Lower Plasma β-Amyloid 1-42 Levels in Amnestic Mild Cognitive Impairment Compared to Healthy Individuals - Cynthia Cynthia; Jusak Nugraha; Muhammad Hamdan; Hari Basuki Notobroto; Silvia Francina Lumempouw; Rahajuningsih Dharma (Indonesian Biomedical Journal)
BACKGROUND: Amnestic mild cognitive impairment (aMCI) is strongly associated with an increased risk of progression to Alzheimer’s disease (AD). In AD, cerebrospinal fluid (CSF) β-Amyloid 1-42 levels are known to decrease, a pattern which is also observed in aMCI. While in AD, apolipoprotein E (ApoE) ε4 allele is known to be a genetic risk factor, the role of ApoE ε4 allele in modulating plasma β-Amyloid 1-42 levels in aMCI remains unclear. Therefore, this study was performed to evaluate plasma β-Amyloid 1-42 levels in aMCI patients compared to cognitively healthy individuals and investigate its association with ApoE ε4 allele.